The effect of corporate bankruptcy reorganization on consumer behaviour - Emerson Wagner Mainardes; Ricardo Lopes Mota; Nadia Cardoso Moreira (European Research on Management and Business Economics (ERMBE), 2020)
The objective of this study is to compare the effects of a company's perceived levels of trust, reputation, risk perception, and quality, on consumers' purchasing intention in two contexts. The first context posits a company in stable financial condition, while the second a company in bankruptcy reorganization. After proposing the theoretical model, we conducted research using two questionnaires, which resulted in 187 respondents for the stable company situation, and 189 who responded to questions about companies undergoing corporate bankruptcy reorganization. The results support our assumptions that the state of a company's financial situation has an effect on the relationship of trust on perceived quality, and reputation on purchase intention. These results lead to the conclusion that an unfavourable financial situation does not generally harm consumer perceptions of the supplier company but may cause changes in perceptions of their trust and reputation.
Keywords: M31; M21; L22; 650; Bankruptcy; Purchase intention; Reputation; Risk